2021
DOI: 10.3329/jdmc.v29i1.51175
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors of the Severity of Dengue Fever: A Cross-Sectional Study in a Tertiary Care Center of Bangladesh

Abstract: Background: Dengue is an endemic disease for Bangladesh with occasional outbreak. Little is known about the predictors of severe dengue. Methods: This cross sectional study was conducted in the medicine department of Dhaka Medical College from April 2019 to March 2020. Total 199 consecutive patients were enrolled in this study. For the purpose of the analysis, dengue fever was classified as group I and dengue hemorrhagic fever and dengue shock syndrome was classified as group II. Results: The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…These findings are in accordance with the previous study who reported more cases of dengue infection in males as compared to females 13 . Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 . Another study carried out by Jaiswal N et al reported that dengue infection occurs more in females as compared to males which in concordance to our findings 14 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These findings are in accordance with the previous study who reported more cases of dengue infection in males as compared to females 13 . Another study carried out by HOSSAIN MZ et al reported more cases of dengue infection in males as compared to females 8 . Another study carried out by Jaiswal N et al reported that dengue infection occurs more in females as compared to males which in concordance to our findings 14 .…”
Section: Discussionmentioning
confidence: 90%
“…The type and intensity of the illness will determine the appearance of other symptoms like rash, gastrointestinal issues like nausea or vomiting, and respiratory tract problems like cough, sore throat, and nasal congestion 7 . Leucopenia, thrombocytopenia, and increasing hematocrit are characteristics of peripheral blood parameters 8 . Many studies have been published on the dengue infection but based on literature very limited research has been carried out on the clinical, demographic and hematological parameters between severe and non-severe dengue infections.…”
Section: Introductionmentioning
confidence: 99%